2022
DOI: 10.1038/s41590-022-01379-9
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia drives CD39-dependent suppressor function in exhausted T cells to limit antitumor immunity

Abstract: Extended Data Fig. 6 | Cd4-driven Cre recombinase expression efficiently deletes CD39 on CD8 + TIL. (a, b) TIL analysis of CD39 and inhibitory expression in CD8 + T cells from Cd4 Cre Entpd1 f/f mice. (c) Cell counts per milligram of tumor mass from experiments in Extended Data Fig. 6a, b. (d) Tumor areas at day 14 from experiments in Fig. 2f. (e) Suppression assay of Cd4 Cre Entpd1 f/f Thy1.1 + CD44 + OT-I T eff cells isolated from day 8 of acute Vaccinia OVA infection. (f) CD39 expression on TIL tT ex cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(77 citation statements)
references
References 53 publications
2
63
0
Order By: Relevance
“…2D). Indeed, recently Vignali et al reported the connection of hypoxia and exhaustion that support the accuracy of our bioinformatics analysis (47). Furthermore, this systemic analysis indicated shared TFs can be a molecular basis of the parallel differentiation trajectories, Naive → MP → TRM and Naive → TexProg → TexTerm, from acute and chronic infection (fig.…”
Section: Discussionsupporting
confidence: 84%
“…2D). Indeed, recently Vignali et al reported the connection of hypoxia and exhaustion that support the accuracy of our bioinformatics analysis (47). Furthermore, this systemic analysis indicated shared TFs can be a molecular basis of the parallel differentiation trajectories, Naive → MP → TRM and Naive → TexProg → TexTerm, from acute and chronic infection (fig.…”
Section: Discussionsupporting
confidence: 84%
“…Indeed, it has been shown that exhausted T cells are not only hypofunctional but can also upregulate molecules that suppress local T cell immunity. Exhausted T cells upregulate CD39 and IL-10 which are both important molecules utilised by regulatory T cells (Tregs) to mediate suppressive functions(31, 32). Consistent with this idea, IGRP-specific cells in NOD-TII mice expressed high levels of IL-10 (Fig 6B) and CD39 (Fig 6C and D), while there was no difference in the frequency of FoxP3 + Tregs between NOD and NOD-TII mice (Fig 6E).…”
Section: Resultsmentioning
confidence: 99%
“…CD39 ( Entpd1 ) is expressed in terminally exhausted T cells (40) and acts via catabolising ATP and ADP to AMP and further degradation to adenosine via CD73. A recent study has shown that CD39 expressing terminally exhausted cells have suppressive capacity similar to conventional FoxP3 expressing CD4+ regulatory T cells(31). Several reports have identified that IL-10 secreting CD8 + T cells play a regulatory role in protecting against autoimmune disease (32, 41, 42).…”
Section: Discussionmentioning
confidence: 99%
“…4 There are many other factors, such as, resistance of targeted cells, metabolic status, hypoxia, etc., may also affect the tempo of exhaustion. 5 Other methods include adoptive T-cell therapy, in which T cells are extracted from the patient, modified, expanded in vitro, and then infused back into the patient to boost their antitumour capabilities. 6,7 Unfortunately, the broad effectiveness of T cell-based cancer therapy in the clinic is still elusive.…”
Section: To Regulate the T-cell Activity In The Tumour Microenvironmentmentioning
confidence: 99%
“…Despite these important advances, only certain subsets of T cells could be reinvigorated 4 . There are many other factors, such as, resistance of targeted cells, metabolic status, hypoxia, etc., may also affect the tempo of exhaustion 5 . Other methods include adoptive T‐cell therapy, in which T cells are extracted from the patient, modified, expanded in vitro, and then infused back into the patient to boost their antitumour capabilities 6,7 .…”
Section: Challenges On Theranostics Of T‐cell Immunoactivitymentioning
confidence: 99%